Bilateral absence of maxillary and mandibular second premolars: a clinical, genetic and dermatoglyphic study - (:unkn) unknown (My University, 1994)
In the report presented here the mode of inheritance pattern of absence of maxillary and mandibular second premolars will be investigated by pedigree analyses and dermatoglyphic studies of a patient who showed the trait and his family members. An 11-year-old male patient with caries with bilateral absence of maxillary and mandibular second premolars was observed. Most of the dermatoglyphic traits observed in the patient were also found in the father and the sister of the patient.
Keywords: Humans; Male; Child; Anodontia; Bicuspid; Pedigree; Dermatoglyphics; Genes, Dominant